2007
DOI: 10.1097/01.prs.0000253445.76991.de
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Tension Sutures in the Prevention of Postabdominoplasty Seroma: A Prospective, Randomized, Double-Blind Clinical Trial

Abstract: Progressive tension sutures increase surgical time, reduce drain outputs, and have the same clinical and ultrasound seroma frequency as the use of drains alone. The combination of both methods simultaneously does not add any advantages. However, complications and interventions increase if at least one of them is not used. The mechanism of action of progressive tension sutures could be the compartmentalization of the fluid collection under the flap facilitating absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 48 publications
2
71
2
5
Order By: Relevance
“…In his series, no patient had a clinically significant fluid collection. Andrades et al, 19 whose study is the only recent randomized, doubleblind, controlled study involving PTS, observed a significant reduction in seroma with PTS relative to controls. Although ultrasonography may demonstrate small collections of fluid, in our experience these collections have not been clinically relevant and they resolve spontaneously without consequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his series, no patient had a clinically significant fluid collection. Andrades et al, 19 whose study is the only recent randomized, doubleblind, controlled study involving PTS, observed a significant reduction in seroma with PTS relative to controls. Although ultrasonography may demonstrate small collections of fluid, in our experience these collections have not been clinically relevant and they resolve spontaneously without consequence.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that there is no advantage to using drains with PTS. 19,20 Moreover, the placement of PTS is more difficult when drains are in the surgical field, which may increase operating time and the surgeon's learning curve.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Further detail was added by Pollock 7 , and the technique was then reproduced by others [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…O mecanismo proposto na sua gênese baseia-se nas lesões vasculares e linfáticas, no desenvolvimento de espaço morto secundário ao descolamento do retalho dermoadiposo e na força de cisalhamento existente entre o retalho e o complexo músculo-aponeurótico 17 . Bozola e Psillakis 16 , em 1988, relacionaram a incidência de seromas com a extensão da cirurgia, tendo as cirurgias de maior porte predisposição aumentada ao desenvolvimento desta complicação.…”
Section: Discussionunclassified